Fluorobenzotriazole (FTAZ)‐Based Polymer Donor Enables Organic Solar Cells Exceeding 12% Efficiency. (18th January 2019) - Liao, Zhihui; Xie, Yuanpeng; Chen, Lie; Tan, Yun; Huang, Shaorong; An, Yongkang; Ryu, Hwa Sook; Meng, Xiangchuan; Liao, Xunfan; Huang, Bin; Xie, Qian; Woo, Han Young; et al.
Abstract: The fluorobenzotriazole (FTAZ)‐based copolymer donors are promising candidates for nonfullerene polymer solar cells (PSCs), but suffer from relatively low photovoltaic performance due to their unsuitable energy levels and unfavorable morphology. Herein, three polymer donors, L24, L68, and L810, based on a chlorinated‐thienyl benzodithiophene (BDT‐2Cl) unit and FTAZ with different branched alkyl side chain, are synthesized. Incorporation of a chlorine (Cl) atom into the BDT unit is found to distinctly optimize the molecular planarity, energy levels, and improve the polymerization activity. Impressively, subtle side chain length of FTAZ realizes a dramatic improvement in all the device parameters, as revealed by the short‐current density ( J sc ) improved from 7.41 to 20.76 mA cm −2, fill‐factor from 36.3 to 73.5%, and even the open‐circuit voltage ( V oc ) from 0.495 to 0.790 V. The best power conversion efficiency (PCE) of 12.1% is obtained from the L810‐based device, which is one of the highest values reported for FTAZ‐based PSCs so far. Notably, the corresponding external quantum efficiency curve keeps a very prominent value up to 80% from 500 to 800 nm. The notable performance is discovered from the reduced energy loss, improved molecular face‐on orientation, the down‐shifted energy levels, and optimized absorption coefficient regulated by side‐chain engineering. Abstract : Three polymers L24, L68, and L810 are developed as donor materials for organic solar cells . As the alkyl side chain of the fluorobenzotriazole (FTAZ) unit increases, the L810‐based device exhibits lower energy loss, better molecular face‐on orientation, and a higher absorption coefficient. Consequently, the power conversion efficiency is improved to 12.1%, which is one of the highest values for FTAZ‐based devices.